Effect of Nano herbal Haramounting (Rhodomyrtus tomentosa) in Histology of Heart Mus musculus - Syafruddin Ilyas (International Journal of Ecophysiology, 2019)
The objective of this study was to determine the effect of histology of heart Mus musculus after giving Nano Herbal Rhodomyrtus tomentosa (Haramonting). R.tomentosa (Haramonting) is made on a nanoscale using High Energy Milling (HEM). This research use the Completely Randomized Design (CRD). Treatment consists of 6 groups, namely: Control: CMC 0.5%; T1:100mg/20gBW; T2: 141,42mg/20gBW; T3:200mg/20gBW; T4: 282,82mg/20gBW; T5:400mg/20gBW. The results of histology hearts that there were significant difference (P<0,05) between control group and treatment groups but there was not significantly different in weight of hearts (P>0,05).